Endophytic Bacteria from Wet Soil of South Kalimantan as Biological Control Agent for Root Nematodes (NPA) in Celery (Apium graveolens) - Marcellino Althaf; Wilujeng Widayati; Arika Purnawati (Future Science, 2022)
Endophytic bacteria are microorganisms that are associated with plants, don’t cause disease, and mutualism associated with plants. One of the uses of endophytic bacteria in agriculture is as biological agent in overcoming the attack of the root-knot nematode Meloidogyne sp. It is a polyphagous parasite that can attack plants by forming galls on the roots of celery plants (A. graveolens), can lack nutrients, and in chronic conditions causes death of host plants. It’s control is important to reduce crop yield loss. Control of the nematode Meloidogyne sp., at this time use many chemical pesticides because they quickly kill nematodes, but the continuous use of chemical nematicides will potentially pollute the environment. So, it is necessary to study alternative control using endophytic bacteria. The purpose of this study was to determine the potential of endophytic bacteria from wetlands of South Kalimantan as biological agents of it in celery plants. This research was conducted in Sumber Glagah, Pacet, Mojokerto, using Completely Randomized Design (CRD). The treatment was carried out by immersing the roots of celery plants in a suspension of endophytic bacteria (24 hours) and concentration (108 cfu/ml), then planted in polybags measuring 30 x 30. The polybags were filled with soil that had been divested with 50 juvenile Meloidogyne sp. Observation parameters were the number of galls per g of roots and juvenile population per g of root and per 10 g of soil. The results showed that the treatment of endophytic bacteria reduce: (1) number gall per g celery roots was 19.67–31.00 and control (46.67); (2) population juvenile population per g root was 9.33-25.67 and control 50.67; (3) juvenile population per 10 g of soil was 11.33-17.00 and control 29.33.